The successful treatment of primary brain echinococcosis - Andriy Sirko; Ihor Kyrpa (Ukrainian Neurosurgical Journal, 2016)
The case of successful treatment of primary brain affection by echinococcus with formation of giant unicameral cyst in patient 28 year-old is documented. Epidemiological data on echinococcosis occurence in the world, in Ukraine, and in Dnipropetrovsk region is specified. Main focus is given to two aspects: preoperative brain echinococcosis diagnosing through noninvasive neuroimaging methods (brain CT and MRT), and the special features of surgical approach aimed at total removal of giant capillary echinococcal cyst without damaging its integrity.Total echinococcal cyst removal using hydrodynamic expulsion method with maximum head bend to the trepanation side without cyst puncturing was proved the optimal treatment method in cyst localization closer to cerebrum cortex. Specific nature of echinococcal cysts lies in the fact that, in case of expansive growth, their chitinous membrane does not grow into brain tissue, but they rather “move the brain tissue apart”. The cyst is easily removed as it is loosely bound to brain cortex. Knowledge of abovementioned brain echinococcal cysts diagnostics and treatment features enables their preoperative detection and total removal.